Evaluación de los Métodos Físico, Químicos y Biológicos para el control de Fusarium spp. En Coriandrum sativum en Lamas- Perú - Inga Mesias, Bequer Misael (2000)
The present investigation work was carried out in Lamas - Perú in the field of a fanner with the following objectives: to evaluate and to detennine tite efficiency of the eradication principie applying three methods combined for the handling of the illness plants death and coriander withered caused by the musbroom Fusarium spp.; and to carry out the economic analysis of benefit I cost of the best treatments. The statistical design was used totally at random, with fifteen treatments and three repetitions: 14 were loting and one was not loting that served as wítness; to twelve treatments loting it was added protection fungicídes, systemic and in mixtures that are Benomil, Tiofanate Metil + Thiram, Captan, Captan+ Flutolanil, Imazalil and Citrex to different dose and two treatments were added controllers of the gender Trichodenna. Germination, inddence ,0f the illness, concentration of the mushrooms bio controllers, height, yield and economic analysis were evaluated. Of all the studied treatments, the more lotíng Captan the 4,0 %11 (T5) he/she gave the best results with a yield of 4 329,55 Kg. /ha, obtaining a gross benefit of S l. 21 647,75 New Suns and the production cost represents ín the benefit 26,25%.